Pengaruh Kepuasan Konsumen dan Variety Seeking terhadap Brand Switching Produk MS Glow ke Produk Somethinc: Studi pada Pengguna di Kecamatan Poleang - Masni Masni; Ismanto Ismanto; Muhamad Stiadi (Jurnal Mahasiswa Manajemen dan Akuntansi, 2026)
This study aims to determine (1) The effect of consumer satisfaction on brand switching from MS Glow products to Somethinc products in Poleang District. (2) The effect of variety seeking on brand switching from MS Glow products to Somethinc products in Poleang District. This study uses a quantitative method approach. Data collection in this study uses Observation, Documentation and Questionnaires. The population of this study is users of Ms Glow products who switch to Somethinc products who are domiciled in Poleang District. While the sample of this study amounted to 110 people. Testing of research instruments using validity tests and reliability tests with SPSS 26.0. The data analysis technique used in this study is the measurement model test (Outer model) and the structural model test (Inner model) with Smart PLS 4.0. Based on the research results, it is known that: (1) There is a negative and significant influence between consumer satisfaction and brand switching as indicated by the Original Sample Estimate value of 0.297 and T-Statistic of 3.887 with a P-Value of 0.000. (2) There is a positive and significant influence between variety seeking and brand switching as indicated by the Original Sample Estimate value of 0.589 and T-Statistic of 7.666 with a P-Value of 0.000.